Is Bladder Training by Clamping Before Removal Necessary for Short-Term Indwelling Urinary Catheter Inpatient? A Systematic Review and Meta-analysis - Li-Hsiang Wang, MSN; Ming-Fen Tsai, PhD; Chin-Yen Stacey Han, PhD; Yi-Chi Huang, MSN; Hsueh-Erh Liu, RN, PhD (Elsevier, 2016)
Purpose: Urinary catheterization is a common technique in clinical practice. There is, however, no consensus on management prior to removal of the indwelling catheter for short-term patients. This systematic review examined the necessity of clamping before removal of an indwelling urinary catheter in short-term patients. Methods: A systematic literature review was conducted using eight databases and predetermined keywords-guided searches. Some 2,515 studies were evaluated. Ten studies that met the inclusion criteria were selected. Results: The quality of the studies was assessed using the Jadad scoring system. Only 40.0% of studies were rated as high quality. This review found that catheter clamping prior to removal was not necessary for the short-term patient. When made a comparison with the unclamping group, there was no significant difference in recatheterization risk, risk of urine retention, patients' subjective perceptions and rate of urinary tract infection. Conclusions: This review indicated that bladder training by clamping prior to removal of urinary catheters is not necessary in short-term catheter patients. In addition, clamping carries the risk of complications such as prolonging urinary catheter retention and urinary tract injury. Further investigation requires higher quality methodologies and more diverse study designs.